Avascular necrosis in children with cerebral palsy after reconstructive hip surgery. (October 2017) - Phillips, L.; Hesketh, K.; Schaeffer, E. K.; Andrade, J.; Farr, J.; Mulpuri, K.
Purpose: Progressive hip displacement is one of the most common orthopaedic pathologies in children with cerebral palsy (CP). Reconstructive hip surgery has become the standard treatment of care. Reported avascular necrosis (AVN) rates for hip reconstructive surgery in these patients vary widely in the literature. The purpose of this study is to identify the frequency and associated risk factors of AVN for reconstructive hip procedures. Methods: A retrospective analysis was performed of 70 cases of reconstructive hip surgery in 47 children with CP, between 2009 and 2013. All 70 cases involved varus derotation osteotomy (VDRO), with 60% having combined VDRO and pelvic osteotomies (PO), and 21% requiring open reductions. Mean age at time of surgery was 8.82 years and 90% of patients were Gross Motor Function Classification System (GMFCS) 4 and 5. Radiographic dysplasia parameters were analysed at selected intervals, to a minimum of one year post-operatively. Severity of AVN was classified by Kruczynski's method. Bivar- iate statistical analysis was conducted using Chi-square test and Student's t-test. Results: There were 19 (27%) noted cases of AVN, all radio- graphically identifiable within the first post-operative year. The majority of AVN cases (63%) were mild to moderate in severity. Pre-operative migration percentage (MP) (p = 0.0009) and post-operative change in MP (p = 0.002) were the most significant predictors of AVN. Other risk factors were: GMFCS level (p = 0.031), post-operative change in NSA (p = 0.02) and concomitant adductor tenotomy (0.028). Conclusion: AVN was observed in 27% of patients. Severity of displacement correlates directly with AVN risk and we suggest that hip reconstruction, specifically VDRO, be performed early in the 'hip at risk' group to avoid this complication.